Case report: Lichenoid esophagitis revealing an HIV infection - Marschner, Jasmin; Schmitt-Graeff, Annette; Kreisel, Wolfgang; Decker, Annegrit; Schauer, Franziska (Frontiers in Medicine, 2024)
Esophageal lichen planus is an underrecognized manifestation of lichen planus. It is typically diagnosed based on characteristic endoscopic findings, such as hyperkeratosis, trachealization, denudation and/ or stenosis, along with the presence of a lichenoid infiltrate in histopathological examination. In cases where no other manifestation of lichen planus are found and direct immunofluorescence for fibrinogen along the basement membrane is negative, the term “lichenoid esophagitis” should be preferred. This distinction is critical, as it prompts a thorough evaluation for underlying diseases, including autoimmune conditions and viral infections. We report a case of a 69-year-old male with stenosing esophagitis resembling esophageal lichen planus on endoscopic evaluation. The condition was refractory to multiple dilation procedures and high-dose proton pump inhibitor therapy. Histopathological analysis revealed a dense lymphocytic infiltrate extending into the epithelial layer, while direct immunofluorescence microscopy for fibrinogen was negative. There were no other signs of lichen planus on the skin or mucous membranes. The patient's medical history included recurrent transient ischemic attack (non-cardiac), penile cancer and recurrent mucosal candidiasis. Laboratory findings revealed Epstein-Barr virus viremia and IgG hypergammaglobulinemia, raising suspicion of immunodeficiency. Further testing confirmed an active HIV infection, classified as category C3 was detected, and antiretroviral therapy was initiated. Following the initiation of antiretroviral therapy, the patient experienced rapid clinical and histopathological improvement of the lichenoid esophageal inflammation, although the esophageal stenosis persisted. Subsequent follow-up endoscopies confirmed resolution of the inflammatory component, underscoring the positive impact of addressing the underlying HIV infection on the esophagus. This case report highlights the importance of recognizing lichenoid esophagitis as a potential diagnosis in cases of unexplained chronic esophagitis, especially when standard treatments are ineffective. The presence of lichenoid inflammation without other manifestation of lichen planus should trigger an investigation into underlying conditions.